A ruined temple to the north of the Mahanaleshwar temple complex - Temples of India Project Team (Jio Institute, 2024)
Similar to the western boundary of the Mahanaleshvar temple complex, the northern side also has two temples that stand close to the Mahanaleshwar Temple. Seen here is one of these temples whose superstructure is lost. The plinth of the temple and the walls have been partially reconstructed. The original temple was designed to have a garbhagriha (sanctum sanctorum), an antarala (vestibule or antechamber) and a mandapa (pillared hall). Based on the remains scattered in the vicinity of the temple, the temple might have had a shikhara of the shekhari (multi-spired) variety. The main shrine was designed to be pancharatha (consisting of five projections).